Plasminogen Activator Inhibitor 1 Contains a Cryptic High Affinity Receptor Binding Site that Is Exposed upon Complex Formation with Tissue-type Plasminogen Activator, - Horn, Ivo R.; van den Berg, Birgit M. M.; Moestrup, Søren K.; Pannekoek, Hans; Zonneveld, Anton-Jan van (Thrombosis and Haemostasis, 1998)
The low density lipoprotein receptor-related protein (LRP), a multifunctional endocytic receptor, mediates the cellular internalization of tissue-type (t-PA) and urokinase-type (u-PA) plasminogen activator and their complexes with plasminogen activator inhibitor type 1 (PAI-1). LRP preferentially binds the complexed forms, exemplified by equilibrium dissociation constants (KD) that are at least an order of magnitude lower than those of the free components. To understand the molecular interactions, underlying the preference of the receptor for complexes rather than for the free components, we have performed a detailed analysis of the affinity and kinetics of the binding of PAI-1 and t-PA:PAI-1 complexes to the receptor, using surface plasmon resonance. To assess the involvement of the heparin-binding domain of PAI-1 for the interaction with LRP, we determined the equilibrium dissociation constants for the binding to LRP of a panel of PAI-1 mutants with single- and multiple amino-acid substitutions of the basic residues that constitute the heparin binding site of PAI-1 (K65, K69, R76, K80 and K88). The binding of these PAI-1 mutants was partially reduced with a 2 to 4 fold increase in KD values for single (K80, K88) and combined (K80, 88) substitution mutant proteins respectively. LRP binding of complexes, composed of t-PA with either wild type PAI-1 or any one of the single PAI-1 mutants indicated a major role of lysine 69 (K69) for the binding of t-PA:PAI-1 complexes to LRP (KD values of 6.1, 3.7, 75.4, 5.4, 12.5 and 8.1 nM for wild type, K65A, K69A, R76A, K80A and K88A complexes, respectively). Since the KD for the binding of free t-PA to LRP is 158 nM, we conclude that the PAI-1 moiety harbors the major determinant for t-PA:PAI-1 complex binding to LRP. The in vitro binding studies were extended by binding and clearance studies with COS-1 cells. Degradation of both 125I-t-PA:PAI-1 K69A and 125I-t-PA:PAI-1 K69A K80A K88A complexes after 2 h of incubation was reduced compared to the degradation of 125I-t-PA:PAI-1 complexes. We conclude that PAI-1 contains a cryptic binding site (lysine 69) for LRP, that is specifically expressed upon t-PA:PAI-1 complex formation.